METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF TICARGRELOR IN BULK AND COMPARISON WITH OTHER PUBLISHED METHODS - BS Muddukrishna (Journal of Global Pharma Technology, 2016)
The following article consist of highly sensitive and easy RP-HPLC method to estimate Ticagrelor in bulk. Ticagrelor was separated using Shimadzu LC-20-AD with auto sampler and PDA/UV detector. The separation was achieved using a C18 Vydac Monomeric 120A (5.0 micron, 250 x 4.6mm) column. Acetonitrile: Water Milli Q (60:40 v/v) at a flow rate of 1.0 ml/min was used as the mobile phase. The method was linear having line equation f(x)=1.90442e-005*x-0.302059 with correlation coefficient (R2) of 0.997. The method was precise having  RSD as 0.27% (intraday precision). The LOD & LOQ were 0.083μg/mL and 0.25μg/mL respectively. The developed method was validated for precision, linearity, system suitability and robustness; hence proves that it is highly applicable to estimate Ticagrelor in day to day analysis.